2001
DOI: 10.1017/s004857720199225x
|View full text |Cite
|
Sign up to set email alerts
|

Striking a chord: Moods, blood pressure, and heart rate in everyday life

Abstract: The objective of this study was to assess the relation between the intensity of single moods and of mood combinations on blood pressure (BP) and heart rate (HR). The subjects were 203 healthy registered nurses, all women, who were studied on two work and two off days. Ambulatory BP and HR were recorded every 20 minutes. On each occasion subjects rated their moods on a 5-point scale. Graded increases in BP and HR were shown with higher ratings of negative moods and decreases for a mood related to energy level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Thus, the findings of the study indicate that change in the context of an experimental environment between one that is primarily alerting (stressing or inducing arousal) and one that is primarily relaxing (habituating or reducing arousal), may change the direction of the associations of systolic blood pressure with severity of depressive symptoms, positive and negative affect. In everyday life, this association may be comparable to other measurement approaches such as the evaluation of the 24-hour cardiovascular activity for its adaptive or maladaptive fluctuation between and within days (e.g., working/nonworking or circadian cycles of arousal) in relation to mood rated across the sampling periods (Shapiro et al, 2001;Davydov et al, 2010a). The present findings are in accord with previous observations showing that i) lower daytime but not night-time systolic blood pressure level is associated with lower positive mood during the day (Davydov et al, 2010a), ii) participants with depression have a significantly greater drop in systolic blood pressure (orthostatic hypotension) when standing from a supine position (Richardson et al, 2009;Vasudev et al, 2011;Perlmuter et al, 2012), iii) patients with higher anxiety or depression showed increase of SBP and/or DBP (white coat effect or white coat hypertension) if readings were taken by a nurse or a physician in the surgery (Bo et al, 2009;Yavuz et al, 2009).…”
Section: Means Of Moodmentioning
confidence: 71%
“…Thus, the findings of the study indicate that change in the context of an experimental environment between one that is primarily alerting (stressing or inducing arousal) and one that is primarily relaxing (habituating or reducing arousal), may change the direction of the associations of systolic blood pressure with severity of depressive symptoms, positive and negative affect. In everyday life, this association may be comparable to other measurement approaches such as the evaluation of the 24-hour cardiovascular activity for its adaptive or maladaptive fluctuation between and within days (e.g., working/nonworking or circadian cycles of arousal) in relation to mood rated across the sampling periods (Shapiro et al, 2001;Davydov et al, 2010a). The present findings are in accord with previous observations showing that i) lower daytime but not night-time systolic blood pressure level is associated with lower positive mood during the day (Davydov et al, 2010a), ii) participants with depression have a significantly greater drop in systolic blood pressure (orthostatic hypotension) when standing from a supine position (Richardson et al, 2009;Vasudev et al, 2011;Perlmuter et al, 2012), iii) patients with higher anxiety or depression showed increase of SBP and/or DBP (white coat effect or white coat hypertension) if readings were taken by a nurse or a physician in the surgery (Bo et al, 2009;Yavuz et al, 2009).…”
Section: Means Of Moodmentioning
confidence: 71%
“…Anxiety and negative affect have distinct autonomic concomitants [25], which may raise IA and provoke the tendency towards overreporting or symptom amplification previously noted by Barsky and Borus [26] and Pennebaker [14]. If proven, this causal chain could potentially beget a vicious spiral wherein anxiety provokes increased IA, which amplifies symptom detection and severity, and subsequently raises the level of anxiety experienced by the individual.…”
Section: Introductionmentioning
confidence: 88%
“…Thus, in our population of young adults, peripheral and central hemodynamic responses do not directly predict current mood or depressive symptoms. Associations between hemodynamic responses and affect seem to be more complicated and may involve compensatory hemodynamic action in other brain regions [52][53][54]. Notwistanding this, taken together, our data suggest that low blood pressure levels, even in young adulthood, are associated with a condition of reduced reactivity to sustained pleasant stimulation, at both subjective and neurobiological levels.…”
Section: Discussionmentioning
confidence: 53%